Students as promoters of rural extension in aquaculture in the Marajó archipelago, Pará, Brazil - Fabricio Nilo Lima da Silva; Raoani Cruz Mendonça; Manoel Luciano Aviz de Quadros; Luã Caldas de Oliveira; Antonia Rafaela Gonçalves Macedo; Osnan Lennon Lameira Silva; Lenilton Alex de Araujo Oliveira (Universidade Federal do Norte do Tocantins, 2020)
Aquaculture is the creation of aquatic organisms. An expanding activity, being of great importance its approach in rural extension. Thus, the objective of this study was to analyze the contribution of extension activities in aquaculture in the professional training of students in Marajó, Amazon, Brazil. The project "Technology transfer through training and technical assistance for tambaqui breeders, Colossoma macropomum, in the archipelago of Marajó/PA" was developed by 10 technician and under graduate students from rural education course and the technical course in aquaculture from the Federal Institute of Education, Science and Technology of Pará (IFPA) Campus Breves, in the city of Curralinho. They participated in the stages of data collection in aquaculture enterprises, training for producers and monitoring of aquaculture production, acting as researchers, instructors and extension workers, respectively. The duration of the project was from August 2019 to March 2020. At the end of the project, a questionnaire was applied to the students involved. The results showed that the aquaculture extension activities developed were relevant and significant, for the construction of knowledge in a mutual way between those involved (students and aquaculture producers). The acquired experiences will substantiate and subsidize the professional practice of these students in a concrete and effective way. In conclusion, the extension project represents an excellent tool in the teaching-learning process for students.